An overview of methods for the treatment and diagnosis of dementia with Lewy bodies. Clinical case analysis - M. Š. Markevičiūtė; M. Karnickas; A. Bagdonaitė (Neurologijos seminarai)
Dementia with Lewy bodies (DLB) is a progressive neurodegenerative, rarely diagnosed dementia of unknown origin that manifests as fluctuations in cognitive function, complex visual hallucinations, parkinsonism, and REM sleep behavior disorder. A distinctive pathological feature of DLB is the multiple Lewy bodies – eosinophilic hyaline inclusions in the cytoplasm of neurons that are detected in the brain at autopsy. Although DLB is the third most common type of dementia in the elderly, after Alzheimer’s disease and vascular dementia, it is still too rarely diagnosed. Meanwhile, diagnosed cases of DLB are often detected late because diagnosis at an early stage is difficult as DLB can present in symptoms similar to Alzheimer’s disease, Parkinson’s disease, vascular dementia, delirium, and other disorders. In this article, by presenting a clinical case of a patient with DLB and discussing the literature and the most recent diagnostic criteria, we seek to remind that patients with DLB experience a wide range of symptoms, including delusions, anxiety, aggression, and depression. We also discuss the latest DLB diagnostic criteria published in 2017, which drew more focus on REM sleep behavior disorder than previously. The main purpose of the article is to remind that the management of DLB is a multidisciplinary task for psychiatrists and neurologists. The treatment of DLB is also complex and challenging due to the high risk of adverse drug reactions. A drug prescribed to control one symptom of the disease may worsen other symptoms. Patients may be exceptionally sensitive to antipsychotics for the control of delirium and hallucinations, therefore pharmacological treatment should be individualized.